The impact of illegal mining on public health: A case study in kenyasi, the Ahafo region of Ghana - Mensah, Ebenezer Owusu; Darku, Edward Delali (Technium Social Sciences Journal, 2021)
Mining is an economic pillar of many countries endowed with natural mineral resources, including gold, diamond, bauxites, and gemstone, among others. Unregulated or illegal mining poses several health risks to people living within or close to mining communities. People living within mining communities across the world have in the past experienced and continue to health threatening, which include respiratory, kidney, musculoskeletal, and skin diseases. This research was conducted in Kenyasi the district capital of Asutifi north district of Ghana to examine the impact of illegal mining on public health A total of 200 respondents were contacted for essential information of which 1oo lives close to mines and other 100 lives far away from mining communities; we identified the former by those who live 10 to 20 kilometers from mining communities whereas far from mining communities were identified by those who live in a neighboring community where mining activities are not in existence. The main research instruments used were questionnaires, interviews, and focus group discussion. Data collected were analyzed using statistical package for social science (SPSS) software. Econometric models such as multiple linear regression model, Mann-U Whitney and Chi-square test were used to analyze data collected. The findings of this study show that inhabitants in the community face numerous challenges such as water, air, and land pollutions from illegal mining activities due to miners’ excessive use of dangerous chemicals like mercury. The study also revealed that individuals close to mines at Kenyasi in the Asutifi north district capital suffered from health problems than their counterpart who live far from mines. The increment of illegal mining in the kenyasi district capital of Asutifi north of Ghana has caused numerous environmental hazards to many individuals and households. Although the negative of illegal mining affects the entire nation; It can be concluded in our study that both miners and non- miners who live close to mining area suffered more health problem which includes vulnerable group (women and children) than those who live far from mining areas